Pengalaman Perempuan Dalam Membangun Dan Mempertahankan Keberlanjutan Karier Di Industri Pertambangan: Sebuah Studi Fenomenologi - Windina Putri Pasaribu; Mirwan Surya Perdhana (Faculty of Economics and Business Diponegoro University, 2026)
The mining industry remains historically male-dominated, shaped by entrenched masculine norms that constrain women’s career sustainability. This study explores the lived experiences of women in the Indonesian mining sector using a qualitative phenomenological approach, drawing on in-depth interviews with ten participants in technical and administrative roles and analyzed through explicitation techniques. The findings reveal that career entry is influenced by the accumulation of human and social capital, alongside strong economic motivations. In practice, women face gendered communication norms, dual legitimacy pressures related to gender and age, as well as horizontal segregation and vertical glass ceiling barriers linked to reproductive life stages. Career sustainability is supported through a combination of formal institutional mechanisms and informal relational solidarity within organizational culture, while participants exhibit resilience through adaptive coping and long-term career planning aligned with life transitions. The study concludes that women’s career sustainability in mining is an active, negotiated process shaped by the interaction between professional aspirations, individual agency, and gendered institutional structures, contributing to the development of gendered organization theory and life-course perspectives in Global South contexts.